Pemanfaatan Citra Satelit Sentinel-2A Untuk Pemetaan Habitat Dasar Perairan Dangkal (Studi Kasus: Teluk Humbolt, Kota Jayapura) - Alfred Dimara; Baigo Hamuna; Lisiard Dimara (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
The waters of Humbolt Bay in Jayapura City have a diversity of habitats in shallow water. The purpose of this study is to map the shallow water habitat in the waters of Humbolt Bay, Jayapura City using Sentinel-2A satellite imagery. This research was conducted from April to May 2019 in several parts of Humbolt Bay, including Kosong Island, Kayupulo Island, and along the coast from Hamadi to Weref. Mapping of shallow water habitat using the supervised classification method with Lyzenga algorithm transformation. The accuracy of the classification results is done by using the confusion matrix method to compare the sample points in the field with the results of the classification of satellite images. Sentinel-2A satellite image data processing results obtained shallow water habitat including live coral, seagrass, dead coral, and sand with an estimated area of about 269.8 Ha, 148.9 Ha, 156.1 Ha, and 87.6 Ha. The results of the accuracy-test analysis showed that the mapping accuracy was 73.77% of the 61 validation points used for the accuracy test.Keywords: Bottom habitat; Sentinel-2A; Supervised; Lyzenga algorithm; Humbolt Bay